Thermo-Hydrodynamic Features of Grooved Heat Sink with Droplet-Shaped Fins Based on Taguchi Optimization and Field Synergy Analysis - Lin Zhong; Jingli Shi; Yifan Li; Zhipeng Wang (Energies)
In recent years, the number of transistors on electronic chips has surpassed Moore’s law, resulting in overheating and energy consumption problems in data centers (DCs). Chip-level microchannel cooling is expected to address these challenges. Grooved heat sinks with droplet-shaped fins were introduced to modify the overall capability of the cooling system. The degree of impact of the distribution of grooves and fins was analyzed and optimized using the Taguchi method. Moreover, the coupling effect of flow and temperature fields was explained using the field synergy theory. The key findings are as follows: for thermal resistance, pump power, and overall efficiency, the influence degree is the number of combined units > number of fins in each unit > distribution of the combined units. The optimal configuration of 21 combined units arranged from dense to sparse with one fin in each unit achieves 14.05% lower thermal resistance and 8.5% higher overall efficiency than the initial heat sink. The optimal configuration of five combined units arranged from sparse to dense with one fin in each unit reduces the power energy consumption by 27.61%. After optimization, the synergy angle between the velocity vector and temperature gradient is reduced by 4.29% compared to the smooth heat sink. The coupling effect between flow and heat transport is strengthened. The optimized configuration can better balance heat dissipation and energy consumption, improve the comprehensive capability of cooling system, provide a feasible solution to solve the problems of local overheating and high energy consumption in DCs.